2022 Update of the Consensus on the Rational Use of Antithrombotics and Thrombolytics in Veterinary Critical Care (CURATIVE) Domain 1‐ Defining populations at risk. Issue 3 (2nd May 2022) - deLaforcade, Armelle; Bacek, Lenore; Blais, Marie‐Claude; Boyd, Corrin; Brainard, Benjamin M; Chan, Daniel L.; Cortellini, Stefano; Goggs, Robert; Hoareau, Guillaume L; Koenigshof, Amy; Li, Ron; Lynch, Alex; et al.
Abstract: Objectives: To expand the number of conditions and interventions explored for their associations with thrombosis in the veterinary literature and to provide the basis for prescribing recommendations. Design: A population exposure comparison outcome format was used to represent patient, exposure, comparison, and outcome. Population Exposure Comparison Outcome questions were distributed to worksheet authors who performed comprehensive searches, summarized the evidence, and created guideline recommendations that were reviewed by domain chairs. The revised guidelines then underwent the Delphi survey process to reach consensus on the final guidelines. Diseases evaluated in this iteration included heartworm disease (dogs and cats), immune‐mediated hemolytic anemia (cats), protein‐losing nephropathy (cats), protein‐losing enteropathy (dogs and cats), sepsis (cats), hyperadrenocorticism (cats), liver disease (dogs), congenital portosystemic shunts (dogs and cats) and the following interventions: IV catheters (dogs and cats), arterial catheters (dogs and cats), vascular access ports (dogs and cats), extracorporeal circuits (dogs and cats) and transvenous pacemakers (dogs and cats). Results: Of the diseases evaluated in this iteration, a high risk for thrombosis was defined as heartworm disease or protein‐losing enteropathy. Low risk for thrombosis was defined as dogs with liver disease, cats with immune‐mediated hemolytic anemia, protein‐losing nephropathy, sepsis, or hyperadrenocorticism. Conclusions: Associations with thrombosis are outlined for various conditions and interventions and provide the basis for management recommendations. Numerous knowledge gaps were identified that represent opportunities for future studies.